Electrophysiological characteristics and catheter ablation of atypical fast-slow atrioventricular nodal reentrant tachycardia using an inferolateral left atrial slow pathway. (3rd October 2022) - Kaneko, Y; Fukuda, K; Irie, T; Shimizu, H; Tamura, S; Kobari, T; Hasegawa, H; Nakajima, T; Ishii, H
Abstract: Background: Understandings of subtypes of atypical atrioventricular nodal reentrant tachycardia (AVNRT) using variants of slow pathway (SP) are still growing. Inferolateral (inf-lat-) left atrial (LA) SP is a rare variant extending into an inf-lat-LA along the mitral annulus (MA). Purpose: To characterize an unknown subtype of atypical fast-slow (F/S-) AVNRT using an inf-lat-LA-SP as a retrograde limb (inf-lat-LA-F/S-AVNRT). Methods: This Japanese multicenter retrospective study enrolled 4 patients of inf-lat-LA-F/S-AVNRT that was characterized by the earliest site of atrial activation during tachycardia (EAA) between 3 and 6 o'clock along the MA. The diagnosis was made by an exclusion of AV reentrant tachycardia (AVRT) and atrial tachycardia (AT) according to the standard criteria and was confirmed by successful elimination of tachycardia and the inf-lat-LA-SP. Results: Surface ECG during tachycardia revealed long RP appearance except one who had short RP due to a short conduction time across the inf-lat-LA-SP. During tachycardia, far-field LA activation preceding near-field activation of coronary sinus (CS) musculature was visible in the CS recording in 2. Retrograde conduction via the inf-lat-LA-SP with a decremental delay was consistently reproducible with ventricular stimulation in 2, 1 of whom had double atrial response, while it was always masked by the presence of a retrograde conduction via the fast pathway in 1 and a retrograde block at the lower common pathway in 1. An injection of a small dose of ATP transiently interrupted a retrograde conduction over the inf-lat-LA-SP, suggesting its ATP-sensitivity. Exclusion of AVRT was made by no resetting of tachycardia with left ventricular extrastimulus in 2 and VA dissociation during overdrive pacing of tachycardia in remaining 2. Exclusion of AT was made by V-A-V response after ventricular entrainment in 1 and termination without atrial capture by ventricular pacing in 2. Ablation of the right-sided SP was unsuccessful to eliminate the tachycardia, but ablation at or near the EAA by transseptal approach was successful to cure the tachycardia, associated with an elimination of a retrograde conduction over the inf-lat-LA-SP following a development of an accelerated junction rhythm in all. Low-frequency potentials preceding local atrial activation, consistent with a retrograde activation via the inf-lat-LA-SP were detected along the MA medial to the EAA in 1. Conclusions: Differential diagnosis of tachycardia with the EAA in the inf-lat-LA and especially long RP appearance should include inf-lat-LA-F/S-AVNRT. Presumed arrhythmogenic substrate of the inf-lat-LA-SP seemed to be consistent with the remnant of embryogenic AV ring tissue in the electropharmacological and locational characteristics. Successful elimination of this AVNRT can be obtained by ablation of the inf-lat-LA-SP, but not of the right-sided SP. Funding Acknowledgement: Type of funding sources: None.